The Mediating Role of Diabetes Distress and Depressive Symptoms in Type 2 Diabetes Medication Adherence Gender Differences. (June 2020) - Aronson, Benjamin D.; Sittner, Kelley J.; Walls, Melissa L.
Background. Medication adherence is negatively related to both diabetes distress (DD) and depressive symptoms (DS). Past research suggests gender differences in adherence, DD, and DS. A gap exists in determining if gender differences in adherence are mediated by DD and DS, or if gender moderates differences in adherence by DD/DS. Aims . This study investigated the relationship between gender, DD, DS, and medication adherence and tested for mediating and moderating effects on medication adherence among American Indian adults with type 2 diabetes. Method . The Maawaji idi-oog mino-ayaawin (Gathering for Health) study was a community-based participatory research collaboration with five American Indian tribes. Participants, randomly recruited from clinic records, shared information during computer-assisted personal interviews. This study includes the 166 participants who reported using medications to treat their diabetes. The relationship between gender, DD, DS, and medication adherence are explored. Possible mediating and moderating effects on medication were tested using regression and path analysis. Results. Females had higher levels of DD and DS and lower levels of medication adherence. Higher levels of DD and DS were both associated with lower medication adherence. No evidence was found that gender moderates the relationship between DD or DS and medication adherence. Instead, DD and DS mediated the relationship between gender and medication adherence. Conclusions . Medication adherence differences in male and female patients may be attributable to DD and DS. The present research highlights both DD and DS as targets for clinicians and researchers alike.